The detection of Japanese encephalitis virus (JEV) in the Murray region, New South Wales: a public health investigation - Shava, Gamuchirai M; Todd, Katherine; Oakman, Tracey; Rahman, Saifur; Hueston, Linda; Glasgow, Keira; Roberts-Witteveen, April (Communicable Diseases Intelligence, 2025)
The detection of Japanese Encephalitis Virus (JEV) in pigs in the Murray Region in February 2022 prompted an urgent public health response by NSW Health for people at greatest risk of infection. As this was the earliest detection of JEV in south-eastern Australia, vaccination was offered to people exposed to the same environment as JEV positive pigs, along with serology collection to assist with the investigation into JEV prevalence in a presumably naïve population. A standardised questionnaire was developed and conducted to collect demographic and exposure information to aid in serology interpretation. The reasons for the emergence of JEV in pigs in the Murray region are unclear, however the findings indicate that transmission to humans is likely.